Analisis Risk Event & Risk Agent pada Proyek Kontruksi Perumahan Citraland Surabaya dengan Metode House Of Risk - Irsyad, Muhammad Alvan Mashuri Al; Triana, Masca Indra (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
Housing development is an important part of the construction sector that often experiences delays. These delays can increase costs, cause problems in contracts, damage buyer confidence, and result in fines and damage the company's reputation. This study uses the HOR (House of Risk) Method, this method is relatively new and can be used to identify and analyze risks and causes and how to minimize the factors causing delays to become alternative preventive measures (risk mitigation). After conducting the study, 8 events were found that had risks and 9 events that caused the risk. From the evaluation results, the risk agent that played the most important role was the low discipline of the workforce in carrying out the work. Then the mitigation action that was considered most appropriate and easy to use was placing workers according to competency (job matching).